Simple parameter-based CAC scheme for DiffServ domain / Husna Zainol Abidin, Norashidah Md. Din and Norsheila Fisal - Zainol Abidin, Husna; Md. Din, Norashidah; Fisal, Norsheila (UiTM Press, 2010)
Future sophisticated Internet applications require strict end-to-end performance guarantees as Internet is no longer meant only for transferring data such as file transfer and email. It is changing into broadband integrated network that should be capable of carrying all sorts of traffics including real time and non real time traffics with different requirements. This is the limitation of normal Internet Protocol (IP) network which cannot guarantee enough resources in order to provide Quality of Service (QoS). This paper focuses on traffic management mechanisms in a QoS model known as Differentiated Services (DiffServ) where a parameter-based Connection Admission Control (CAC) scheme is deployed in a DiffServ network. The proposed scheme is based on the mathematical analysis of peak bandwidth, effective bandwidth and mean bandwidth.